Los pliegues del sinclinal de tunja. análisis estructural y modelamiento geométrico (1997)
The Tunja syncline is located at the northern termination of the Altiplano of the Eastern Cordillera, which constitutes a distinct physiographic province in the central part of the Eastern Cordillera between the cities of Bogota and Tunja. Together with its bordering basement cored anticlines, the Arcabuco and Toca anticline, it belongs to the Cordillera's first-order structures which are characterized by longitudinal continuities of several hundred kms and display, as a further outstanding feature, an eastern vergence. Superposed on this large scale disposition, trains of second-order folds with lengths of 100 km or less form the next important oroqraphlc features. Some structural independence from the basement-cored structures is documented by their vergences which, at least in the Tunja syncline, consistently oppose the first-order dip directions. The fact that they attain higher amplitudes above the steeply inclined segments of the western flank of the Tunja syncline, suggests an origin by gravity sliding. Yet the observed strain pattern does not unambiguously supports a model of simple detachment folds, as a neutral or even extensive regime at a higher structural level gives way to increasingly compressive deformations at low structural levels. These relations argue for a model in which amplification of the folding occurs at the cost of a homogeneous shortening near the basement-cover contact. A linear geometric extrapolation between oberved surficial folds and a supposedly unfolded basement-cover interface predicts a strain pattern, which is in good agreement with the observed deformations. A third-order, small scale folding affects only strata which have been eroded across anticlinal crests. These structures present themselves as flaps or cascade folds with vergences according to the dip direction of the higher order folds. For their origin a gravitational collapse during a latest stage of the folding process may be advocated.